1999
DOI: 10.1002/(sici)1521-379x(199904)51:4<126::aid-star126>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Distribution and Pasting Properties of UV-Irradiated Corn Starches

Abstract: Suspension (30 %, w/w) of corn starch (25 % amylose) in water was irradiated by UV‐light with wavelength greater than 250 nm at 25°C, under a stream of nitrogen or air, for time intervals ranging from 5 to 25 h. Effects of the irradiation on the transition enthalpy and temperature for melting, and the pasting viscosity profile of the irradiated starch were examined. Weight‐average molecular weight (Mw) and radius of gyration (Rg) of the irradiated starch molecules were measured by high performance size exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 10 publications
1
23
2
Order By: Relevance
“…The UV irradiation of corn starch slurries under nitrogen depolymerised the starch, whereas such irradiation under oxygen induced photodegradation followed by recombination of generated polysaccharide radicals. 4 An increase in the water binding capacity and solubility of starch exposed to UV light was noted 8 together with a decrease in the hot paste viscosity. 1,4 The crystalline structure 2 and gelatinisation enthalpy 4,9 of starches did not change, although the intrinsic viscosity decreased.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The UV irradiation of corn starch slurries under nitrogen depolymerised the starch, whereas such irradiation under oxygen induced photodegradation followed by recombination of generated polysaccharide radicals. 4 An increase in the water binding capacity and solubility of starch exposed to UV light was noted 8 together with a decrease in the hot paste viscosity. 1,4 The crystalline structure 2 and gelatinisation enthalpy 4,9 of starches did not change, although the intrinsic viscosity decreased.…”
Section: Introductionsupporting
confidence: 60%
“…4 An increase in the water binding capacity and solubility of starch exposed to UV light was noted 8 together with a decrease in the hot paste viscosity. 1,4 The crystalline structure 2 and gelatinisation enthalpy 4,9 of starches did not change, although the intrinsic viscosity decreased. 9,10 Induction of depolymerisation-repolymerisation reactions of polysaccharide molecules in normal corn, potato and waxy corn starches illuminated with linearly polarised visible light was reported in our previous papers.…”
Section: Introductionmentioning
confidence: 95%
“…However, UV irradiation did not change the rheological properties of corn starch. These results are not concordant with those of a previous study [12] which found a decrease in viscosity from 90 to 65 RVU after UV irradiation of a corn starch suspension.…”
Section: Expansion Propertiesmentioning
confidence: 99%
“…The treatment of starch with UV radiation induces changes in its functional properties, such as increases in water binding capacity and solubility, and decreases in hot paste viscosity [16]. The usage of a combined method, like the one realised by this study (UV radiation ?…”
Section: Introductionmentioning
confidence: 99%